Penentuan Wilayah Basis untuk Pengembangan Usaha Perikanan Tangkap Ramah Lingkungan di Perairan Pulau Salahnama dan Pulau Pandang - Mustaruddin Mustaruddin; Asnil Asnil (Jurnal Ilmu Pertanian Indonesia, 2020)
Approximately 34.1% of marine fish production in Tanjung Tiram, Batubara Regency comes from the waters of Salahnama Island and Pandang Island. The development of fishing effort in environmentally-friendly ways in the appropriate locations can guarantee the continuity of fish production and to provide a space for the development of the other management activities. The study aims to analyze the type of environmentally-friendly fishing effort and determine the location quotient for their developments in the waters of Salahnama Island and Pandang Island. The methods used were descriptive method, scoring analysis, and analysis of location quotient (LQ). The results showed that fish traps, hook and line, gillnet, and falling net were selected as environmentally-friendly fishing efforts. The location quotients for their developments are a) Fish traps in the east waters and north of Salahnama Island; b) Hook and line in the east waters of Salahnama Island and the north waters of Pandang Island; c) Gillnet in the east waters and north of Salahnama Island and the east waters of Pandang Island; and d) Falling net in the west waters of Salahnama Island and Pandang Island. The location quotient for development to their supporters are a) Port in the south area of Salahnama Island and the west area of Pandang Island and b) Fuel installation in the west area of Salahnama Island and Pandang Island. Keywords: batubara, fishing effort, location quotient, environmentally-friendly